Prinsip Penginjilan Berdasarkan 1 Korintus 9:16 dan Relevansinya bagi Tugas Guru PAK - Simarangkir, Sunggul; Angkouw, Semuel Ruddy; Kuntari J, Valentina Dwi (DIDASKO: Jurnal Teologi dan Pendidikan Kristen, 2022)
This paper specifically describes the Principles of Evangelism Based on I Cor. 9:16 and Its Relevance for Teachers of Christian Religious Education. This topic is discussed to explain factually the principles of evangelism for teachers. Christian religious education has not been fully implemented in the classroom, in the field and to people who do not believe in Jesus Christ. This topic is discussed considering that there are still many unreached tribes in the ministry of evangelism. Of course, this responsibility is not only borne by the mission agency, the church. However, religious institutions include Christian religious education teachers to reach tribes that have not yet perfected the Bible. In describing this topic, the researcher uses a qualitative method with an exegesis approach. The results of this study describe that the principle of evangelism is expressed in an attitude of not being arrogant, then evangelism as a duty and responsibility of believers and evangelism should be used as a lifestyle. To PAK teachers, it is hoped that there will be efforts to increase understanding of evangelism and be responsible for directing students to manifest this attitude in community, church and school life as mandated by Jesus Christ, as the Great Teacher.AbstrakTulisan ini secara spesifik menguraikan perihal Prinsip Penginjilan Berdasarkan I Kor. 9:16 dan Relevansinya bagi Pengajar Pendidikan agama kristen. Topik ini dibahas untuk menjelaskan secara faktual dalam prinsip penginjilan bagi pengajar Pendidikan agama kristen belum sepenuhnya di terapkan di dalam kelas, dilapangan dan kepada orang yang belum percaya kepada Yesus Kristus. Topik ini dibahas mengigat masih banyak ditemukan berbagai suku belum terjangkau dalam pelayanan penginjilan. Tentunya tugas tanggung jawab ini bukan hanya dibebankan kepada lembaga misi, gereja. Namun lembaga keagamaan termasuk pengajar pendidikan agama kristen untuk menjangkau suku yang masih belum sempurnakan Injil. Di dalam menguraikan topik ini, peneliti menggunakan metode kualitatif dengan pendekatan Eksegese. Hasil penelitian ini menguraikan bahwa prinsip penginjilan yaitu dinyatakan pada sikap tidak sombong, kemudian penginjilan sebagai tugas dan tanggung jawab orang percaya dan penginjilan hendaknya dijadikan sebagai gaya hidup. Kepada guru PAK, diharapkan adanya upaya untuk meningkatkan pemahaman tentang penginjilan serta bertanggung jawab dalam mengarahkan anak didik untuk mewujudkan sikap tersebut dalam kehidupan bermasyarakat, gereja dan sekolah sebagaimana dimanatkan oleh Yesus Kristus, sebagai Guru Agung.